Managing Deep Learning Implementation in Elementary Schools: Its Influence on Students’ Learning Outcomes - Khoridatul, Desi; Chaidir, Rahmayanti; Mardalena (Al-Qalam Institue, 2026)
This study aims to analyze the effect of deep learning implementation on elementary students’ learning outcomes from a learning management perspective. Deep learning is understood as a pedagogical approach that promotes meaningful learning through active student engagement, critical and reflective thinking, collaboration, and strengthened conceptual understanding, aligning with the demands of 21st-century education. The study employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. The research participants were fifth-grade students who experienced a structured deep learning process before progressing to the next grade level. Data were collected using a standardized cognitive achievement test with adequate content validity and high reliability (Cronbach’s Alpha > 0.80). Statistical analyses included descriptive statistics, the Shapiro–Wilk normality test, and a paired sample t-test. The results revealed a significant improvement in students’ learning outcomes after the implementation of deep learning, as indicated by a statistically significant difference between pretest and posttest scores (p < 0.05). These findings imply that deep learning can serve as an effective instructional strategy that strengthens learning management practices, particularly in planning, implementing, and evaluating instruction to improve learning quality in elementary education.